First case report: near early T-cell precursor acute lymphoblastic leukemia with plasmacytoid dendritic cell proliferation effectively treated with Venetoclax plus HAG regimen - Jiongping Han; Dan Li; Hongqiang Luo; Zhe Chen; Yi Feng; Fang Liu; Liping Wang; Xin Huang; Weiying Feng (Hematology)
Background: Near early T-cell precursor acute lymphoblastic leukemia represents a distinct subtype of T-cell acute lymphoblastic leukemia characterized by specific immunophenotypic and molecular biological characteristics. Currently, no standardized treatment protocol exists.Methods: This study presents a case of near early T-cell precursor acute lymphoblastic leukemia (ETP-ALL) characterized by plasmacytoid dendritic cell proliferation, which manifested clinically through pancytopenia and generalized multiple rashes.Results: The patient underwent successful treatment with chemotherapy consisting of Venetoclax combined with HAG regimen administered for one cycle.Discussion: This case report provides preliminary evidence suggesting that the combination of Venetoclax with HAG (homoharringtonine, cytarabine, and granulocyte colony-stimulating factor) regimen may constitute an effective and tolerable therapeutic approach for patients with near ETP-ALL. However, these initial observations necessitate further validation through comprehensive clinical studies with larger sample sizes to definitively establish the treatment's efficacy and safety profile.